HUBUNGAN ASUPAN PROTEIN,VITAMIN A,VITAMIN E,DAN ZINK DENGAN KADAR ALBUMIN PADA PASIEN KANKER PAYUDARA DI RUMAH SAKIT TUGUREJO SEMARANG - Prisma Nurahmatika; Sufiati Bintanah; Hapsari Sulistya Kusuma (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2017)
Preface: The life quality of breast cancer patients become an attention from several overseas institution. The decreasing life quality of breast cancer patient mostly caused by nutrition alteration resulting of weight loss and decreasing level of albumin.  The level of albumin on breast cancer patients is important because it is a parameter of nutriotional status. The purpose of this study is to know the correlation between protein intake, food source of vitamin A, vitamin E and zinc with albumin level on breast cancer inpatient in Tugurejo Hospital Semarang Research Method :This study is explanatory research that aiming to breast cancer inpatient in Tugurejo Hospital Semarang.Correlation analysis of variables is using pearson correlation Research Results: There is correlation between intake of protein and zinc with respondent’s albumin level (Protein p:0,034; Zink:0,033).There is no correlation between intake of vitamin A, vitamin E with respondent’s albumin level (vitamin A p:0,542 ;vitamin E: 0,468) . Conclusion : Protein and zinc intake may affect the albumin levels. Vitamin A and  Vitamin E  intake cannot affect the albumin  Keywords: albumin, protein intake, vitamin a, vitamin e, zinc breast cancer